EFFECT OF LIGHT AND MEDIUM INTENSITY BRAIN GYMNASTICS ON THE IMPROVEMENT OF COGNITIVE FUNCTION IN ELDERLY - Parellangi Parellangi; Rina Loriana; Rivan Firdaus (Belitung Nursing Journal, 2018)
Background: Decreased brain aging is due to impaired cognitive function. One effort to inhibit cognitive decline due to aging is by doing brain gym. Objective: This study aims to examine the effect of light and medium intensity brain gymnastic on the improvement of cognitive function of elderly, and compare its result between the two intervention. Methods: This was an experimental research with pre-test and post-test group design conducted in 2016. There were 66 people included in this study, which 33 randomly assigned in the light intensity brain gymnastic group (group I) and medium intensity brain gymnastic group (group II). Mini Mental State Examination (MMSE) questionnaires was used to measure cognitive function of elderly. Data were analyzed using univariate and bivariate analysis. Bivariate analysis used paired t-test and independent sample t-test. Results: Findings of this study reveal that there was a significant effect of light and medium intensity brain gymnastic on the improvement of cognitive function of elderly (p=0.000). However, light intensity brain gymnastics (mean= 6.61) is better in improving the cognitive function of the elderly compared with medium intensity brain gymnastics (mean 2.18), with p=0.000, respectively. Conclusions: Brain gymnastic with light intensity for 10 minutes per exercise with frequency of 3 times a week is more effective in improving the cognitive function of the elderly compared with brain gymnastic with medium intensity for 15 minutes per exercise with frequency of two times a week.